Compact four-element SRR-loaded dual-band MIMO antenna for WLAN/WiMAX/WiFi/4G-LTE and 5G applications - Sarkar, D; Srivastava, K.V (Electronics letters, 2017)
A four-element dual-band MIMO configuration consisting of split-ring resonator (SRR)-loaded inverted L-monopole antenna elements is realised. In the proposed antenna, the lower-frequency mode of the unloaded MIMO configuration merges with one SRR-induced antenna resonance. This leads to antenna operation around 2.93 GHz with wide impedance bandwidth (IBW) of 35.21%, encompassing the lower WLAN, worldwide interoperability for microwave access, wireless fidelity, fourth generation (4G)-long-term evolution and sub-6 GHz 5G bands. Furthermore, due to SRR loading, the proposed MIMO antenna exhibits a resonance at 5.68 GHz (IBW 6.86%), covering the upper WLAN band. Minimum inter-element isolation of 14 dB is achieved, in spite of the compact total area ($0.103λ _0^2 $0.103λ02, λ0 = highest operating wavelength) and the presence of inter-connected ground plane. Both the working bands exhibit directional radiation patterns with average gain $ ≈ 4\, {\rm dBi}$≈4dBi. Experiments on the fabricated antenna prototype confirm that the simulated and measured S-parameters, radiation patterns (envelope-correlation coefficient, channel capacity loss and total active reflection coefficient) are in good agreement.